Identification and characterisation of a Theileria annulata proline‐rich microtubule and SH3 domain‐interacting protein (TaMISHIP) that forms a complex with CLASP1, EB1, and CD2AP at the schizont surface. (3rd April 2018) - Huber, Sandra; Karagenc, Tulin; Ritler, Dominic; Rottenberg, Sven; Woods, Kerry
Abstract: Theileria annulata is an apicomplexan parasite that modifies the phenotype of its host cell completely, inducing uncontrolled proliferation, resistance to apoptosis, and increased invasiveness. The infected cell thus resembles a cancer cell, and changes to various host cell signalling pathways accompany transformation. Most of the molecular mechanisms leading to Theileria ‐induced immortalization of leukocytes remain unknown. The parasite dissolves the surrounding host cell membrane soon after invasion and starts interacting with host proteins, ensuring its propagation by stably associating with the host cell microtubule network. By using BioID technology together with fluorescence microscopy and co‐immunoprecipitation, we identified a CLASP1/CD2AP/EB1‐containing protein complex that surrounds the schizont throughout the host cell cycle and integrates bovine adaptor proteins (CIN85, 14‐3‐3 epsilon, and ASAP1). This complex also includes the schizont membrane protein Ta‐p104 together with a novel secreted T. annulata protein (encoded by TA20980), which we term microtubule and SH3 domain‐interacting protein (TaMISHIP). TaMISHIP localises to the schizont surface and contains a functional EB1‐binding SxIP motif, as well as functional SH3 domain‐binding Px(P/A)xPR motifs that mediate its interaction with CD2AP. Upon overexpression in non‐infected bovine macrophages, TaMISHIP causes binucleation, potentially indicative of a role in cytokinesis.